BUDIDAYA IKAN NILA DENGAN SISTEM KERAMBA JARING APUNG (KJA) PADA LAHAN BEKAS TAMBANG PASIR (STUDI KASUS KEL. KALUMEME, KEC. UJUNG BULU, KAB. BULUKUMBA) - Abdul Haris; Dedi Azhari Amir (OCTOPUS : JURNAL ILMU PERIKANAN, 2017)
Factors physics of a body of water becomes one of determining the success of the tilapia fish farming system of floating net cages. An environmental parameter that determines the exact location for the cultivation is temperature, depth, brightness, turbidity. The procedure of this study includes (1) preparation, (2) determining the observation station, (3) variable observations, (4) data processing, (5) analysis of descriptive data. Physical parameters of water quality for fish farming tilapia with Keramba cage system (KJA) on mined land in the Village Kalumeme sand, Bulukumba is eligible to serve for cultivation where an increase in growth rate and survival rate of tilapia.